1990
DOI: 10.1037/0021-843x.99.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Peer-group association and adolescent tobacco use.

Abstract: Mosbach & Leventhal (1988) examined the relation of cigarette smoking to peer-group identification in rural Wisconsin adolescents. They found that among dirts (problem-prone youth), regulars (average youth), hot-shots (good social or academic performers), and jocks (athletes), youth most likely to smoke were dirts and hot-shots. We performed a replication with a Southern California cohort and also for use of smokeless tobacco. We hypothesized that jocks would be the main users of smokeless tobacco. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 9 publications
6
85
1
1
Order By: Relevance
“…Some studies show that popular students tend to have higher rates of risk behaviors 28 , and explain that this may be the result of more opportunities to adopt such behaviors because of the larger social network. However, this is controversial, and other studies suggest that having many friends would be a protective factor against risk behaviors 29 . PeNSE showed that not having friends leads to the use of tobacco and other illicit drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that popular students tend to have higher rates of risk behaviors 28 , and explain that this may be the result of more opportunities to adopt such behaviors because of the larger social network. However, this is controversial, and other studies suggest that having many friends would be a protective factor against risk behaviors 29 . PeNSE showed that not having friends leads to the use of tobacco and other illicit drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have examined the typical health-risk behaviors of members of various crowds (e.g., Hussong, 2002;Miller et al, 2003;Sussman et al, 1990). Dolcini and Adler (1994) found that "elites" (a crowd that subsumed both popular and athletic teens) were significantly more likely to have had sexual intercourse than their peers.…”
Section: Jock Identity Vs Athletic Participationmentioning
confidence: 99%
“…For example, Brown and colleagues have constructed a developmental model of peer group affiliation that locates adolescents within a complex network of social crowds (e.g., druggies/burnouts, brains, preppies, nerds) that are both relational and reputational in nature (Brown et al, 1986;Brown et al, 1994). Although the constellation of crowds varies somewhat, virtually all extant models of adolescent crowd affiliation have prominently featured the "jock" crowd, sometimes in isolation and sometimes as part of a larger elite or "popular" group.A number of researchers have examined the typical health-risk behaviors of members of various crowds (e.g., Hussong, 2002;Miller et al, 2003;Sussman et al, 1990). Dolcini and Adler (1994) found that "elites" (a crowd that subsumed both popular and athletic teens) were significantly more likely to have had sexual intercourse than their peers.…”
mentioning
confidence: 99%
“…Specifically, information on adolescent peer crowds indicates the degree to which teens affiliate with reputation-based peer groups across different levels of peer status (e.g., "jocks," "populars," "brains, " "burnouts"). This ecologically valid assessment captures information on teens' social standing among peers and is associated significantly with a variety of risk-taking and internalizing outcomes (Brown & Lohr, 1987;Sussman et al, 1990). Peer crowd assessment also provides information on deviant peer affiliation, which has been associated with several suicide-related domains of adjustment, including adolescents" delinquent, impulsive, and substance use behavior (Dishion et al, 1995); however, deviant peer affiliation has not been linked with suicidal ideation.…”
mentioning
confidence: 99%